rre37 Overexpression Alters Gene Expression Related to the Tricarboxylic Acid Cycle and Pyruvate Metabolism in Synechocystis sp. PCC 6803 - Hiroko Iijima; Atsuko Watanabe; Junko Takanobu; Masami Yokota Hirai; Takashi Osanai (The Scientific World Journal)
The tricarboxylic acid (TCA) cycle and pyruvate metabolism of cyanobacteria are unique and important from the perspectives of biology and biotechnology research. Rre37, a response regulator induced by nitrogen depletion, activates gene expression related to sugar catabolism. Our previous microarray analysis has suggested that Rre37 controls the transcription of genes involved in sugar catabolism, pyruvate metabolism, and the TCA cycle. In this study, quantitative real-time PCR was used to measure the transcript levels of 12 TCA cycle genes and 13 pyruvate metabolism genes. The transcripts of 6 genes (acnB, icd, ppc, pyk1, me, and pta) increased after 4 h of nitrogen depletion in the wild-type GT strain but the induction was abolished by rre37 overexpression. The repression of gene expression of fumC, ddh, and ackA caused by nitrogen depletion was abolished by rre37 overexpression. The expression of me was differently affected by rre37 overexpression, compared to the other 24 genes. These results indicate that Rre37 differently controls the genes of the TCA cycle and pyruvate metabolism, implying the key reaction of the primary in this unicellular cyanobacterium.